Digital-Based Business Development Strategy with a Pentahelix Approach (Case Study of Bolen Bunda Ibra Rantau Prapat) - Harahap, Indah Uzrisa; Syahbudi, Muhammad; Aslami, Nuri (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The purpose of this study was to determine the digital-based business development strategy with a pentahelix approach at Bolen Bunda Ibra in Rantau Prapat. The background of the problem raised is the challenges faced by micro, small and medium enterprises (MSMEs) in utilizing digital technology to increase competitiveness in the industrial era 4.0. The novelty of this research lies in the application of the pentahelix model which involves collaboration between government, academics, businesses, communities, and the media in developing effective digital strategies. This research uses the SOAR (Strengths, Opportunities, Aspirations, Results) analysis method which is a development of SWOT analysis and QSPM (Quantitative, Strategic, Planning, Matrix) matrix. It is suggested that the importance of collaboration between stakeholders in encouraging the digital transformation of MSMEs, as well as the need for policy support and training to improve the digital literacy of bolen bunda ibra rantauprapat business actors.